The Effect of Flake Production and In Vitro Digestion on Releasing Minerals and Trace Elements from Wheat Flakes: The Extended Study of Dietary Intakes for Individual Life Stage Groups - Sumczynski, Daniela; Fišera, Miroslav; Salek, Richardos Nikolaos; Orsavová, Jana (Nutrients, 2023)
This thorough study analyses the amounts of 43 minerals and trace elements in non-traditional wheat grains, flakes, and undigested flake portions using ICP-MS and establishes declines in their respective contents after the flake production. It also identifies appropriate dietary intakes, in vitro digestibility values, retention factors, and metal pollution indexes. The element contents in wheat flakes are lower than in wheat grains after the hydrothermal treatment process, and their declines are: Na (48-72%), Ce (47-72%), Sr (43-55%), Tl (33-43%), Ti (32-41%), U (31-44%), Ho (29-69%), Cr (26-64%), Zr (26-58%), Ag (25-52%), and Ca (25-46%). The flakes significantly contributed to the recommended dietary intake or adequate intake of particular elements for men of all categories as follows: Mn (143%) > Mo > Cu > Mg ≥ Cr > Fe (16%); for women: Mn (up to 183%) > Mo > Cu > Cr ≥ Mg > Fe (7-16%); for pregnant women aged 19-30: Mn (165%) > Mo > Cu > Mg > Cr (25%); and finally, for lactating women: Mn (127%) > Mo > Cu > Mg > Cr (17%). The contributions to the provisional tolerable weekly or monthly intakes of all toxic elements were established as being within the official limits. The daily intakes for non-essential elements were also calculated. The retention factors were calculated to assess the element concentrations in the undigested part using the digestibility values (87.4-90.5%). The highest retention factors were obtained for V (63-92%), Y (57-96%), Ce (43-76%), Pb (34-58%), Tl (32-70%), Ta (31-66%), and Ge (30-49%). K, Mg, P, Zn, Ba, Bi, Ga, Sb, Cu, Ni, and As appear to be released easily from flake matrices during digestion. The metal pollution index has been confirmed as being lower for non-traditional wheat flakes when compared with grains. Importantly, 15-25% of the metal pollution index assessed for native flakes remains in the undigested flake portion after in vitro digestion.
Keywords: essential trace element; Pregnancy; Humans; metal pollution index; přijímání potravy; Metals; Eating; Digestion; wheat flake; dietary intake evaluation; Female; stopové prvky; pšenice; lidé; kovy; mineral; Minerals; ženské pohlaví; laktace; Male; in vitro digestion; trávení; těhotenství; Trace Elements; life stage group; Triticum; disease prevention; retention factor; mužské pohlaví; Lactation; toxic trace element; minerály